2022
DOI: 10.1101/2022.08.11.503624
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Merging Bioactivity Predictions from Cell Morphology and Chemical Fingerprint Models Using Similarity to Training Data

Abstract: The applicability domain of machine learning models trained on structural fingerprints for the prediction of biological endpoints is often limited by the diversity of chemical space of the training data. In this work, we developed similarity-based merger models which combined the output of individual models trained on cell morphology (based on Cell Painting) and chemical structure (based on chemical fingerprints). Using a combination of a decision tree and logistic regression models on the structural versus mo… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

5
2

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 55 publications
0
10
0
Order By: Relevance
“…Other studies using similar ML methodologies compared bioactivity predictions based on Cell Painting and chemical structure information. 80,81 Prediction accuracies for targets like β-catenin (usually assayed using a specific stain) were better when using a BMF Macau model with Cell Painting profiles as side information (F1 score = 0.87) compared to a model using only chemical structural data (F1 score = 0.48). 80 Another study showed that the models that combined structural information and Cell Painting profiles, using similarities to training data, improved the AUC by 16.3% compared to models that only used chemical structure information.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies using similar ML methodologies compared bioactivity predictions based on Cell Painting and chemical structure information. 80,81 Prediction accuracies for targets like β-catenin (usually assayed using a specific stain) were better when using a BMF Macau model with Cell Painting profiles as side information (F1 score = 0.87) compared to a model using only chemical structural data (F1 score = 0.48). 80 Another study showed that the models that combined structural information and Cell Painting profiles, using similarities to training data, improved the AUC by 16.3% compared to models that only used chemical structure information.…”
Section: Discussionmentioning
confidence: 99%
“…80 Another study showed that the models that combined structural information and Cell Painting profiles, using similarities to training data, improved the AUC by 16.3% compared to models that only used chemical structure information. 81…”
Section: Cell Painting In Assay Activity Predictionmentioning
confidence: 99%
“… 47 We started from previous work 14 that employs random forest models trained on a combination of Morgan fingerprints, 23 Cell Painting, 24 and gene ontology features to classify molecules as toxic or nontoxic. Although similar approaches for combining data have been shown to improve accuracy on a range of bioactivity predictions, 48 this approach needs to be established individually for each bioactivity endpoint studied. When using this strategy to find compounds targeting αS, we failed to identify compounds that were both efficacious and nontoxic.…”
Section: Introductionmentioning
confidence: 99%
“…To leverage the advantages of both these approaches and overcome their respective limitations, we propose a computational pipeline in the spirit of active learning. Our approach builds upon previous work showing the positive impact of employing multimodal compound descriptors for bioactivity prediction. , In a first step, initial models are built based on structural information and images, respectively. Then predictions from the image-informed and chemistry-informed ligand-based models guide the selection of molecules to be tested in an actual physical assay.…”
Section: Introductionmentioning
confidence: 99%